Determinação de cobre em cerveja por espectrometria de absorção atômica com chama após microextração líquido-líquido dispersiva - Silveira, Jader Rodrigo Kappaun da (2022)
In this work, a sample preparation method was developed using the dispersive liquidliquid microextraction (DLLME) for the Cu extraction and pre-concentration in beer, followed by the determination by flame atomic absorption spectrometry (F AAS). Unlike the conventional DLLME, where a dispersive solvent and an extraction solvent are mixed, only the extracting solvent was injected into the beer. For the DLLME optimization for Cu extraction, some parameters such as type of extracting solvent and its volume, sample volume, pH, concentration of sodium diethyldithiocarbamate as a complexing agent and the viability of ultrasound in the dispersion were evaluated. After optimization, the external calibration curve was linear between 5 and 100 µg L-¹ Cu, with a limit of quantification of 9,1 µg L-¹ . Accuracy was evaluated for 3 samples and the results were compared with those obtained after microwave-assisted sample digestion and subsequent Cu determination by inductively coupled plasma mass spectrometry and inductively coupled plasma optical emission spectrometry. The method was applied to 7 beer samples and the Cu concentration ranged from 20,6 and 58,8 µg L -¹ . Accuracy was also evaluated by analyte spike, which ranged from 92 to 116%, with relative standard deviation from 3 to 16%. The proposed method for the Cu extraction and pre-concentration from beer by DLLME and quantification by F AAS proved to be suitable in terms of linearity, accuracy and precision, presenting as positive aspects the speed, simplicity of operation and low reagents consumption.